Analysis of Factors Affecting Compliance with the Use of Clinical Pathways in Hospitals: Literature Review - Yulius Adhi Pramono Yoel; Catharina Dwiana Wijayanti (GLOBAL HEALTH SCIENCE GROUP, 2025)
Regulation of the Minister of Health of the Republic of Indonesia Number 30 of 2022 has set 13 national indicators of hospital quality, one of which is compliance with clinical pathways. Clinical pathway is implemented to reduce practice variation and perform evidence-based clinical actions in healthcare facilities, operational efficiency and quality, to achieve the goals of decreased care framing, optimized cost-effectiveness, improved patient outcomes and improved patient and family education regarding the care and treatment received. Objective: To analyze the compliance factors of using clinical pathway in hospital. Methods: This research method is a literature review study using PRISMA. The databases used as sources consisted of Google Scholar, Science Direct and ProQuest. This study used the PICOT strategy in searching articles in electronic databases. From 695 journals, 13 relevant journals were found. Results: Compliance factors for the use of clinical pathways in hospitals can be grouped into two, namely: 1) Adherence to clinical pathway which is influenced by factors: (a) the existence of job satisfaction in the application of clinicians according to clinical pathway, (b) training programs, (c) the formation of specialist teams, (d) organizational factors (leadership, attitudes and motivation) and (e) expanding the role of health workers. 2). Clinical pathway non-compliance is influenced by factors: (a) medical personnel are not involved in the implementation of the use of clinical pathways, (b) management policies that do not work in the use of clinical pathways, (c) lack of socialization to staff related to the use of clinical pathways, (d) there are no clinical pathway documentation guidelines including how to fill in and the benefits and functions of using clinical pathways, (e) increasing workloads. Conclusions: Analysis of compliance factors for the use of clinical pathways in hospitals can be grouped into two, namely compliant and non-compliant. Factors Medical staff compliant using clinical pathway due to job satisfaction, implementation of training programs, formation of specialist teams, organizational factors and expanding the role of health workers. While health staff factors are not compliant with using clinical pathway in the hospital because medical staff are not involved in the implementation of the use of clinical pathway, management policies that do not work in the use of clinical pathway, lack of socialization to staff related to the use of clinical pathway, and there are no clinical pathway documentation guidelines including how to fill and the benefits and functions of using clinical pathway and increase workload.